1969
DOI: 10.1073/pnas.64.3.849
|View full text |Cite
|
Sign up to set email alerts
|

THE “9 + 1” PATTERN OF MICROTUBULES IN SPERMATOZOA OF Mesostoma (PLATYHELMINTHES, TURBELLARIA)

Abstract: Abstract.-The living spermatozoa of the flatworm Mesostoma georgianum have a sperm body about 100 u long and 0.5 , wide, and two motile free flagella, ca. 200 A long. In sections examined with the electron microscope, these flagella have the usual nine pairs of peripheral doublet microtubules and have a single central core unit which is connected to the A members of the doublets by spokelike structures. There are also short connections between the doublets and the flagellar membrane. In material negatively sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 8 publications
(1 reference statement)
1
20
0
1
Order By: Relevance
“…Connections between the microtubules and the cell membrane were observed in the head (Fig. 1B) as has been described for other turbellarians (Silveira & Porter, 1964;Henley et al, 1969;Hendelberg, 1975) and the frog lung fluke (Burton, 1972). In the space between microtubules, board-like structures were sometimes seen (Fig.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Connections between the microtubules and the cell membrane were observed in the head (Fig. 1B) as has been described for other turbellarians (Silveira & Porter, 1964;Henley et al, 1969;Hendelberg, 1975) and the frog lung fluke (Burton, 1972). In the space between microtubules, board-like structures were sometimes seen (Fig.…”
Section: Resultssupporting
confidence: 73%
“…We conjecture also that the connection between the third arm and the flagellar membrane comes about as a result of shrinkage of the diameter of the flagellum, this diameter being smaller after the spermatozoa leave the testis and mature. Henley et al (1969) have diagrammed straight The branching at the distal tip of the flagella of both PO. sapporo and Ph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Trepaxonemata, the central cylinder is made of two helically wound elements (Henley et al 1969;Silveira 1969Silveira , 1975Thomas 1975), while in Childia-Mecynostomidae sperm this structure is represented by a single microtubule and shows no helical pattern in longitudinal sections. Iomini et al (1995) demonstrated that the central axonemal element of Trepaxonemata does not contain tubulin, while the central part of the 9 + 1 axonemal core in C. groenlandica and C. cycloposthium was found to show positive reaction to the three anti-tubulin antibodies used.…”
Section: Discussionmentioning
confidence: 99%
“…Toutefois des exceptions au sch6ma 9 + 2 ont 6t6 signal6es; elles portent, soit sur le nombre de doublets p6riph6riques (48,2,12,39,47,43,8,65), soit sur le nombre de fibres axiales (57,2,58,13,36,11,26,40,28), soit sur la presence de microtubules ~ l'ext6rieur des doublets p6riph6-riques (2,39,47,40,18,7).…”
Section: Introductionunclassified